Mozambique : Economic Rehabilitation and the Poor - Lopes, Paulo; Sacerdoti, Emilio (Washington, D.C. : International Monetary Fund, 1991)
Poverty has remained widespread in Mozambique, mostly on account of the prevalent war situation. This paper provides a profile of the lowest income groups in Mozambique and examines how they were affected by the economic recovery program of 1986-90. The results, indicate that despite large price adjustments, in real terms minimum and low wages improved over the 1986-90 period. Agricultural production increased in response to better incentives, and small farmers in safe areas improved their relative income position. However, in the presence of a large refugee population and war-related destruction, there continues to be a pressing need for extended emergency aid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet